2019
DOI: 10.3389/fpsyg.2019.00328
|View full text |Cite
|
Sign up to set email alerts
|

Stock Market Exposure and Anxiety in a Turbulent Market: Evidence From China

Abstract: The stock market in China has experienced significant turbulence since July 2014, including a bull market. In this paper, we propose that exposure to stock (defined as the condition of being exposed to both stock and stock-related information) can induce anxiety disorder when the market is in a turbulent period. To examine this prediction, we designed two studies in which we operationalized exposure to stock in two different ways. In Study 1, a panel analysis of a longitudinal data set for the Chinese stock ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Previous research has suggested that capital market evolution exhibits strong impact on traders' emotional states 3 , but is also associated with the welfare of individuals who have no direct involvement in the stock market 4 . More specifically, it has been suggested that stock market turbulence is linked to increased anxiety 5 , self-harm and suicide rates 6 8 , elevated levels of binge drinking 9 and fatal car accidents 9 , 10 in the society. These effects may be particularly pronounced in long-lasting socioeconomic events, such as the 2008 stock market crash or the economy slowing in the COVID19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has suggested that capital market evolution exhibits strong impact on traders' emotional states 3 , but is also associated with the welfare of individuals who have no direct involvement in the stock market 4 . More specifically, it has been suggested that stock market turbulence is linked to increased anxiety 5 , self-harm and suicide rates 6 8 , elevated levels of binge drinking 9 and fatal car accidents 9 , 10 in the society. These effects may be particularly pronounced in long-lasting socioeconomic events, such as the 2008 stock market crash or the economy slowing in the COVID19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Our study was motivated by previous ndings demonstrating signi cant relationships between economic indicators and population well-being, particularly evident in turbulent times [1][2][3][4][5][6][7][8][9] . Our study is the rst to show that both mood and brain are highly sensitive to the bellwether of societal change, namely the stock market.…”
Section: Discussionmentioning
confidence: 99%
“…Here we show that these dynamics may originate in scale-free behaviour occurring in many complex systems in nature 45 . Despite being small on an individual level, these effects may have a large in uence on a population level, as the previous studies have suggested [4][5][6][7][8]10 . This is underscored by our objective measure of diastolic blood pressure that in average differed ve units between the samples measured during the lowest market outcomes compared with the ones measured during the highest market outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this idea, previous research has suggested that changes in capital market evolution exhibit a strong impact on traders’ emotional states 3 , and are associated with the welfare of individuals who have no direct involvement in the stock market 4 . Moreover, it has been suggested that stock market turbulence is linked to increased anxiety 5 , self-harm and suicide rates 6–8 , elevated levels of binge drinking 9 and fatal car accidents 9,10 . These effects may be particularly pronounced in long-lasting financial crises, such as the 2008 stock market crash or the economy slowing in the COVID19 pandemic.…”
Section: Introductionmentioning
confidence: 99%